Mutation in PLK4, encoding a master regulator of centriole formation, defines a novel locus for primordial dwarfism. Issue 12 (15th October 2014) - Shaheen, Ranad; Al Tala, Saeed; Almoisheer, Agaadir; Alkuraya, Fowzan S
Abstract : Background: Primordial dwarfism (PD) is a heterogeneous clinical entity characterised by severe prenatal and postnatal growth deficiency. Despite the recent wave of disease gene discovery, the causal mutations in many PD patients remain unknown. Objective: To describe a PD family that maps to a novel locus. Methods: Clinical, imaging and laboratory phenotyping of a new family with PD followed by autozygosity mapping, linkage analysis and candidate gene sequencing. Results: We describe a multiplex consanguineous Saudi family in which two full siblings and one half-sibling presented with classical features of Seckel syndrome in addition to optic nerve hypoplasia. We were able to map the phenotype to a single novel locus on 4q25-q28.2, in which we identified a five base-pair deletion in PLK4, which encodes a master regulator of centriole duplication. Conclusions: Our discovery further confirms the role of genes involved in centriole biology in the pathogenesis of PD.